Constructing "the beginning" : discourses of creation science - Locke, Simon (LEA's communication series., 1999)
"Creation science is a view of the origin of life that rejects the theory of evolution in favor of the book of Genesis in the Old Testament. This claim of scientific status for a religious belief seems to contradict basic tenets of the discrete natures of science and religion. In Constructing "The Beginning," Locke offers a new approach to considering the enigma of creation science, using the perspective of discourse analysis." "Using the publications of the British Creation Science Movement to perform a detailed analysis of the creationist case, Locke demonstrates that the discourses and rhetorics used by natural and social scientists are also employed by nonscientists. Out of this study, a view of science as a cultural resource develops, questioning the adequacy of perceived sociological wisdom that sees science as the source and embodiment of cultural "rationalization."" "As a case study of the use of science as a discursive resource in everyday life, Constructing "The Beginning" speaks to scholars of discourse analysis, constructionism, rhetorics, and the public understanding of science. It will also be of great interest in the areas of cultural studies, sociology of scientific knowledge and of religion, postmodernism, and sociological theory."--Jacket